Khái niệm về mô hình logic đối xứng hệ thống niềm đặc tính - Vân, Phan Chí (Journal of Computer Science and Cybernetics, 2016)
In this paper the autor exposes the concept on the system of characteristic regions which are the set of the elements are the same certain qualities. The author also exposes the concepts of symmetric logical model and the isomorphism between them. These concepts are the enlargement of the concepts on symmetric logical schema and the isomorphism between them.